Classical and quantum dissipative systems - Razavy, Mohsen (World Scientific, 2017)
"Dissipative forces play an important role in problems of classical as well as quantum mechanics. Since these forces are not among the basic forces of nature, it is essential to consider whether they should be treated as phenomenological interactions used in the equations of motion, or they should be derived from other conservative forces. In this book, we discuss both approaches in detail starting with the Stoke's law of motion in a viscous fluid and ending with a rather detailed review of the recent attempts to understand the nature of the drag forces originating from the motion of a plane or a sphere in the vacuum caused by the variations in the zero-point energy. In the classical formulation, mathematical techniques for the construction of Lagrangian and Hamiltonian for the variational formulation of non-conservative systems are discussed at length. Various physical systems of interest including the problem of radiating electron, the theory of natural line width, spin-boson problem, scattering, and trapping of heavy ions and optical potentials models of nuclear reactions are considered and solved. Readership: Researchers and graduate students in applied mathematics and theoretical physics"